2019
DOI: 10.1016/j.hpb.2019.02.021
|View full text |Cite
|
Sign up to set email alerts
|

Implementation and first results of a mandatory, nationwide audit on liver surgery

Abstract: Background: The Dutch Hepato Biliary Audit (DHBA) was initiated in 2013 to assess the national quality of liver surgery. This study aimed to describe the initiation and implementation of this audit along with an overview of the results and future perspectives. Methods: Registry of patients undergoing liver surgery for all primary and secondary liver tumors in the DHBA is mandatory. Weekly, benchmarked information on process and outcome measures is reported to surgical teams. In this study, the first results of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 29 publications
0
23
1
Order By: Relevance
“…However, HPB surgery is an invasive treatment and perioperative morbidity is high, especially for large and complex pancreatic and hepatic procedures. A recent study in patients registered in the obligatory national Dutch audit reported that 43% of the patients had a complicated postoperative course after major liver resection (3 segments) and 26% after minor liver resection (<3 segments) performed for colorectal liver metastasis [6]. Additionally, the Dutch Institute for Clinical Auditing (DICA) reported that between 2014 and 2018, 29% of the patients who underwent a pancreatoduodenectomy in the Netherlands developed a major complication (Clavien-Dindo grade 3) [7].…”
Section: Improving Perioperative Care: Enhanced Recovery After Surgerymentioning
confidence: 99%
“…However, HPB surgery is an invasive treatment and perioperative morbidity is high, especially for large and complex pancreatic and hepatic procedures. A recent study in patients registered in the obligatory national Dutch audit reported that 43% of the patients had a complicated postoperative course after major liver resection (3 segments) and 26% after minor liver resection (<3 segments) performed for colorectal liver metastasis [6]. Additionally, the Dutch Institute for Clinical Auditing (DICA) reported that between 2014 and 2018, 29% of the patients who underwent a pancreatoduodenectomy in the Netherlands developed a major complication (Clavien-Dindo grade 3) [7].…”
Section: Improving Perioperative Care: Enhanced Recovery After Surgerymentioning
confidence: 99%
“…Additionally, there remains a dilemma for the hepatobiliary pathway. The efficiency of the care pathway in terms of diagnostic procedures against the importance of meeting the patient before making a treatment plan at the MDTM so that the patient’s wishes concerning treatment can get more attention and can be optimally included [ 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…Surgery is an important treatment modality for patients with liver or pancreatic tumors; however, perioperative morbidity is high, especially in patients scheduled for liver or pancreatic surgery with a low aerobic fitness. 1,2,4,5 Enhancing preoperative physical fitness of these high-risk patients may improve their postoperative outcomes. Dunne et al showed that a four-week supervised hospitalbased exercise prehabilitation program improved the VO 2 at the ventilatory anaerobic threshold on average with 1.5 ml/kg/min (p=0.023) before liver resection in the intervention group, with no statistically significant difference in any postoperative outcomes compared to the control group.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study reported that 43% of the patients had a complicated postoperative course after major liver resection (≥3 segments) and 26% after a minor liver resection (<3 segments) for colorectal liver metastasis. 1 Additionally, the Dutch Institute for Clinical Auditing (DICA) reported that between 2014 and 2018, 29% of the patient's developed a major complication after pancreaticoduodenectomy. 2 Preoperative aerobic fitness has been found to have a consistent relation with postoperative outcome after major elective intra-abdominal surgery (e.g., morbidity).…”
Section: Introductionmentioning
confidence: 99%